Studi Perbandingan Luas Bidang Tanah Hasil Identifikasi Foto Udara dengan Pengukuran Terestris dalam Menunjang Kegiatan Pendaftaran Tanah Sistematik Lengkap (PTSL) - Pamungkas, Bagas Oriza Pramudya; Arifin, Dawamul; Sutaji, Ahmad Aris Mundir; Insanu, Radik Khairil (Journal of Geomatics Engineering, Technology, and Science, 2024)
This study aims to compare and evaluate the accuracy of land area measurement through aerial photo identification with direct field/ terestrial measurements using Geodetic GPS. This is useful for determining the most efficient and accurate method to support the acceleration of the Complete Systematic Land Registration (PTSL) program. Based on the measurement activities and data analysis, the largest coordinate discrepancy between aerial photo identification and direct measurement using Geodetic GPS was found in land parcel 10, with a difference of 0.88031550. The smallest discrepancy was observed in land parcel 7, with a difference of 0.06694568. The total coordinate discrepancy across the measurement of 10 land parcels was 3.92, with an average discrepancy of 0.35. The Root Mean Square Error (RMSE) value was 0.59. Furthermore, the field measurement results showed that direct field measurement using Geodetic GPS produced highly accurate land area data. The discrepancy between the land area proposed by the applicant and the direct measurement results had an average difference of only 0.7 m². Meanwhile, the measurement results of land area through aerial photo identification showed a larger average discrepancy compared to the land area proposed by PTSL applicants, with an average difference of 10.8 m².